Resorcinol Crystallization from the Melt: A New Ambient Phase and New "Riddles". - Zhu, Q.; Shtukenberg, A.; Carter, Damien; Yu, T.; Yang, J.; Chen, M.; Raiteri, Paolo; Oganov, A.; Pokroy, B.; Polishchuk, I.; Bygrave, P.; Day, G.; et al. (American Chemical Society, 2016)
Structures of the a and ß phases of resorcinol, a major commodity chemical in the pharmaceutical, agrichemical, and polymer industries, were the first polymorphic pair of molecular crystals solved by X-ray analysis. It was recently stated that "no additional phases can be found under atmospheric conditions" (Druzbicki, K. et al. J. Phys. Chem. B 2015, 119, 1681). Herein is described the growth and structure of a new ambient pressure phase, e, through a combination of optical and X-ray crystallography and by computational crystal structure prediction algorithms. a-Resorcinol has long been a model for mechanistic crystal growth studies from both solution and vapor because prisms extended along the polar axis grow much faster in one direction than in the opposite direction. Research has focused on identifying the absolute sense of the fast direction-the so-called "resorcinol riddle"-with the aim of identifying how solvent controls crystal growth. Here, the growth velocity dissymmetry in the melt is analyzed for the ß phase. The e phase only grows from the melt, concomitant with the ß phase, as polycrystalline, radially growing spherulites. If the radii are polar, then the sense of the polar axis is an essential feature of the form. Here, this determination is made for spherulites of ß resorcinol (e, point symmetry 222, does not have a polar axis) with additives that stereoselectively modify growth velocities. Both ß and e have the additional feature that individual radial lamellae may adopt helicoidal morphologies. We correlate the appearance of twisting in β and ε with the symmetry of twist-inducing additives.